IDEOLOGI NASIONALISME DALAM TUTURAN UPACARA BENDERA: ANALISIS WACANA KRITIS WODAK PADA SISWA SMA - Elmirna, Nora; Rahma, Ulfa; Hermoyo, R. Panji (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2026)
Nationalism is often considered a natural characteristic, yet it is routinely produced through educational institutions to shape students' collective identity. The main focus of this research is to examine the construction of nationalist ideology in the speech of the flag ceremony at SMA Negeri 02 Bombana using Ruth Wodak's Critical Discourse Analysis model of Discourse-Historical Approach. The research stages were conducted qualitatively through the process of transcribing the speech of the ceremony instructor, field observations, and in-depth interviews to understand the institutional context. Data analysis focused on discursive strategies that include aspects of nomination, predication, argumentation, perspectivization, and the intensification and mitigation of meaning. The research findings indicate that nationalism is constructed through the framing of the inclusive identity of "we" as the subject of the nation who bears moral responsibility. This narrative dominates all segments of the ceremony with an emphasis on the topos of obligation and the threat of being left behind to legitimize students' compliance with school rules. Furthermore, institutional power relations are disguised through the use of paternalistic greetings that make ideological instructions feel like nurturing advice. The main conclusion confirms that the flag ceremony functions as a mechanism for reproducing state ideology that is normative and sacred in nature within the educational ecosystem. This discursive practice successfully transformed critical awareness into disciplinary compliance without any open resistance through very intensive and systematic national symbolism in a sustainable manner to create pure loyalty among all students. ABSTRAK Nasionalisme sering kali dianggap sebagai karakter yang alami, padahal ia diproduksi secara rutin melalui institusi pendidikan guna membentuk identitas kolektif siswa. Fokus utama penelitian ini adalah mengkaji konstruksi ideologi nasionalisme dalam tuturan upacara bendera di SMA Negeri 02 Bombana dengan menggunakan Analisis Wacana Kritis model Discourse-Historical Approach milik Ruth Wodak. Tahapan penelitian dilakukan secara kualitatif melalui proses transkripsi tuturan amanat pembina upacara, observasi lapangan, serta wawancara mendalam untuk memahami konteks institusional. Analisis data difokuskan pada strategi diskursif yang mencakup aspek nominasi, predikasi, argumentasi, perspektivisasi, serta intensifikasi dan mitigasi makna. Temuan penelitian menunjukkan bahwa nasionalisme dibangun melalui pembingkaian identitas inklusif "kita" sebagai subjek bangsa yang memikul tanggung jawab moral. Narasi tersebut mendominasi seluruh segmen upacara dengan penekanan pada topos kewajiban dan ancaman ketertinggalan guna melegitimasi kepatuhan siswa terhadap aturan sekolah. Selain itu, relasi kuasa institusional disamarkan melalui penggunaan sapaan paternalistik yang membuat instruksi ideologis terasa sebagai nasihat pengasuhan. Simpulan utama menegaskan bahwa upacara bendera berfungsi sebagai mekanisme reproduksi ideologi negara yang bersifat normatif dan sakral dalam ekosistem pendidikan. Praktik diskursif ini berhasil mengubah kesadaran kritis menjadi kepatuhan disipliner tanpa adanya resistensi terbuka melalui simbolisme nasional yang sangat intensif dan sistematis secara berkelanjutan guna menciptakan loyalitas murni pada seluruh peserta didik.